Modelling of dispersive PT-symmetric Bragg grating - Phang, Sendy; Vukovic, Ana; Susanto, Hadi; Benson, Trevor M.; Sewell, Phillip (2014)
This paper reports on the time-domain numerical model of a parity-time Bragg grating with saturated and dispersive gain. The model is compared against the ideal PT scenario where the gain is constant and unsaturated for all frequencies.